Sheltered Income: Estimating Income Under-Reporting in Canada, 1998 and 2004 - Geoffrey R. Dunbar; Chunling Fu (Bank of Canada, 2015)
We use data from the Survey of Financial Security and the Survey of Household Spending to estimate the incidence and extent of income under-reporting in Canada in 1998 and 2004. We estimate that the proportion of households under-reporting income is roughly 35 to 50 per cent in both years. Our estimates also suggest that the amount of under-reported income rose by roughly 40 per cent between 1998 and 2004 and remained stable as a proportion of GDP of 14 to 19 per cent. We find evidence that income underreporting is pervasive and is not confined to households that report self-employment income in the survey data. We also find that poverty measures that rely on reported income appear unreliable because under-reporting necessarily implies a lower reported income. Thus, households that under-report appear to be poorer. We propose a simple ratio method of identifying households that under-report income using the household's budget share on shelter.
Keywords: H26; I32; K42; 330; Domestic demand and components